STRESS INTENSITY FACTOR FOR CRACKED FLAT-ELLIPTIC CROSS-SECTION PIPE - LI Chong; XIE YuJun (Jixie qiangdu)
As an important parameter to assess the crack pipe fracture toughness,stress intensity factor determined is particularly important. In order to solve practical engineering problems,most of them are three-dimensional crack problems,crack mouth widening energy release rate based on the principle of virtual work and bending theory,i. e. G*integral theory is proposed to solve the problem of flat-elliptic cross section cracked pipe with boundary,and the stress intensity factors which are related to G*integral are given under tensile load for flat-elliptic cross-section tube crack. The results show application of this method is simple,and closed-form solution can be obtained.